Gardar Eide Einarsson : [Versuchsstation des Weltuntergangs] - Einarsson, Gardar Eide; Bergen Kunsthall, Bergen; Nickas, Robert; Land, Nick; Herbert, Martin; Sekkingstad, Steinar; Øvstebø, Solveig (Berlin : Sternberg Press, 2013)
The artist's first comprehensive monograph, the book contains documentation of a large selection of works since the early 2000s. Three commissioned essays provide various approaches to the reading of Einarsson's oeuvre. Bob Nickas situates the reader in a science-fiction-inspired future scenario where a book that turns out to be an exhibition catalogue forms the basis for the attempts of the main characters to penetrate into the artist's universe of signs. The philosopher Nick Land outlines a complex interpretative horizon in the encounter with Einarsson's precise analyses of the language of power by exploiting and reactivating the vocabulary of "post-Minimalist" art. And Martin Herbert tackles Einarsson's output in the 2000s, and shows how he continually problematizes the residual potential of art as critique and political tool.--Supplied by publisher.
This is the way the world ends. Never / Bob Nicklas -- This is not a drill / Nick Land -- How to spoil your ballot / Martin Herbert.
Catalog publ. to accompany the exhibition presented at Bergen Kunsthall, Norway, from May 23 to Aug. 15, 2013.
film
Keywords: Einarsson, Gardar Eide